2001
DOI: 10.1093/humrep/16.7.1469
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after cytoplasmic transfer in a couple suffering from idiopathic infertility: Case report

Abstract: Couples suffering from idiopathic infertility are among the most difficult to treat in IVF cycles due to the unknown cause of failure to reproduce. This can lead to years of unsuccessful attempts to conceive and often the abandonment of treatment. In some couples, the only observable problem is the development of poor quality embryos. In this case report, we describe the successful use of cytoplasmic donation in a couple where the high level of embryo fragmentation and poor embryo development was thought to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 20 publications
2
45
0
2
Order By: Relevance
“…Following donor cytoplasmic transfer during ICSI, improvements were observed in embryo formation, implantation, and live births [7681]. Patient selection was not based solely upon maternal age but rather on those who had previously demonstrated poor embryo cleavage rates and morphological anomalies.…”
Section: Third Party Cytoplasmic Transfermentioning
confidence: 99%
“…Following donor cytoplasmic transfer during ICSI, improvements were observed in embryo formation, implantation, and live births [7681]. Patient selection was not based solely upon maternal age but rather on those who had previously demonstrated poor embryo cleavage rates and morphological anomalies.…”
Section: Third Party Cytoplasmic Transfermentioning
confidence: 99%
“…It has been suggested that the introduction of a small amount of ooplasm from a healthy donor oocyte might rescue the function of oocytes that may have certain ooplasm deficiencies [1]. Ooplasm transfer has been attempted in humans and a few pregnancies have resulted [2][3][4]. However, it is not yet fully clear how ooplasm transfer works.…”
Section: Introductionmentioning
confidence: 99%
“…Des expériences de transfert de cytoplasme, chez l'animal, entre un ovocyte donneur normal et un ovocyte de mauvaise qualité ont montré qu'il était possible de restaurer chez ces derniers un potentiel dévelop-pemental normal [30]. Si de nombreux composants cytoplasmiques (substrats énergétiques, protéines, ARN messagers) peuvent être à l'origine de ce phénomène de «sauvetage», les mitochondries jouent probablement un rôle essentiel [31] puisque le transfert de mitochondries purifiées est, à lui seul, capable d'augmenter la production d'ATP de l'ovocyte receveur [32] et de prévenir l'apoptose ovocytaire [33]. Il ne semble pas y avoir de réplication de l'ADNmt avant l'implantation embryonnaire.…”
Section: Mitochondrie Et Développement Embryonnaireunclassified